1995
DOI: 10.1017/s0952523800006787
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical evidence for an axonal localization of GABA in the optic nerves of rabbits, rats, and cats

Abstract: We have examined, by light-microscopic immunocytochemistry, the distribution of GABA in the optic nerves of adult rabbits, rats, and cats. Within the optic nerves, immunoreactivity for GABA was restricted to a small subset of axons; some axons were strongly labelled, others weakly labelled, whilst most axons were unlabelled. Glia and other non-neuronal elements were always unlabelled. Our ability to detect GABA in optic nerve axons of adult mammals contrasts with previous reports that indicate a lack of GABA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…High concentrations of neurotransmitter such as GABA and glycine are also present in a sub-population of mature WM axons in several species (Carlton et al, 1996;Davanger et al, 1991;Rogers and Pow, 1995;Todd and Sullivan, 1990;van den Pol and Gorcs, 1988;Wilson et al, 1996). Block of GABA uptake mimics the effects of GABA upon axon conduction in the neonatal rat optic nerve (Sakatani et al, 1991), while block of catecholamine uptake mimics the effect of nor-adrenaline (Nikolaeva et al, 2009); observations consistent with tonic operation of functional neurotransmitter uptake in the tissue.…”
Section: Gaba and Glycinementioning
confidence: 63%
“…High concentrations of neurotransmitter such as GABA and glycine are also present in a sub-population of mature WM axons in several species (Carlton et al, 1996;Davanger et al, 1991;Rogers and Pow, 1995;Todd and Sullivan, 1990;van den Pol and Gorcs, 1988;Wilson et al, 1996). Block of GABA uptake mimics the effects of GABA upon axon conduction in the neonatal rat optic nerve (Sakatani et al, 1991), while block of catecholamine uptake mimics the effect of nor-adrenaline (Nikolaeva et al, 2009); observations consistent with tonic operation of functional neurotransmitter uptake in the tissue.…”
Section: Gaba and Glycinementioning
confidence: 63%
“…However, in our hands, this antibody produces much higher proportion of GABA-labelled MGP neurones, and we found robust staining of neurones in control tissue, such as the thalamic reticular nucleus. Furthermore, one of us (Rogers and Pow, 1995) has also demonstrated that in the visual system, the sensitivity of this antibody has allowed detection of GABA at sites where it was not previously known to be present.…”
Section: Discussionmentioning
confidence: 99%
“…The antibodies have been used and published (Pow and Crook, 1993;Pow et al, , 1995Pow and Robinson, 1994;Rogers and Pow, 1995;Pow and Rogers, 1996;Pow and Barnett, 1999;Arckens et al, 2000;Kha et al, 2000), and a comparison of the sensitivity of the antibodies has been discussed. Nonspecific labelling of neurones by glutamate antisera seems unlikely because the level of nonspecific staining was determined by omitting either the primary or secondary antibody.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the growth cones of cultured postnatal rat forebrain GABAergic neurons release GABA despite the absence of immunoreactivity for the vesicular component proteins P65 and synaptophysin (Taylor et al, 1990). In the developing visual system, high levels of GABA immunoreactivity are found in the neonatal rat optic nerve astrocytes and axons prior to the development of any vesicular release machinery (Sakatani et al, 1992;Rogers and Pow, 1995). Together, these data indicate that GABA is released from developing neurons before the onset of synaptic vesicles.…”
Section: Discussionmentioning
confidence: 73%